(untitled) (Journal of Oriental Studies, 2016)
This article is made comprehensive analysis of the novel Gao Xinjiang «Bible lonely soul». Author of the novel, the first winner of the award nobel from China in the field of literature. This autobiographical novel, which describes the author’s life from early childhood through historical events took place in the country during the «cultural revolution».